PENGARUH KUALITAS PELAYANAN DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN PADA KLINIK TERAPI ZONA CABANG BINTARO - Ragil Septiana; Dewi Ningsih (Program Studi Akuntansi Fakultas Ekonomi dan BisnisUniversitas Nusa Nipa, 2025)
This research aims to determine and analyze the influence of Service Quality and Consumer Satisfaction on Consumer Loyalty at the Bintaro Branch Zone Therapy Clinic. The research method used is causal associative with a quantitative approach. The population in this study was 134 respondents who were members of the Bintaro Branch Zone Therapy Clinic which will be owned in 2023. The sample for this research was determined using the Purposive Sampling technique and obtained 57 respondents. Hypothesis testing in this research uses panel data regression analysis using the SPSS 24 program and the confidence level used is 5% or 0.05. Based on the calculation results of the t-test results for the service quality variable (X1), it has a significance level of 0.000, this value is smaller than 0.05 (0.000 < 0.05) with a t-calculated value of 2.916 > 2.006. Thus it can be concluded that H01 is accepted and Ha1 is accepted. This means that there is a partial influence of service quality on consumer loyalty at the Bintaro Branch Zone Therapy Clinic. Based on the calculation results of the t test results, the consumer satisfaction variable (X2) has a significance level of 0.000, this value is smaller than 0.05 (0.000 < 0.05) with a t-calculated value of 2.445 > 2.006. It can be concluded that H02 is accepted and Ha2 is accepted. This means that there is no partial influence of consumer satisfaction on consumer loyalty at the Bintaro Branch Zone Therapy Clinic. Based on the calculation results of the F test results, it is known that the significant value for the influence of service quality (X1), consumer satisfaction (X2) on consumer loyalty (Y) is 0.000 < 0.05, the F-calculated value is 4.748 > F-table 3.17 so it can be concluded that H3 is accepted, which means that there is simultaneous service quality and consumer satisfaction on consumer loyalt